The Short Tandem Repeat of the DMT1 Gene as a Molecular Marker of Elite Long-Distance Runners. (23rd November 2019) - Wuyun, Gerile; Hu, Yang; He, Zihong; Li, Yanchun; Yan, Xu
Abstract : The DMT1 gene encodes divalent metal transporter 1, a membrane iron transport protein. Divalent metal transporter 1 influences cellular iron availability, which might further affect aerobic exercise capacity. Short tandem repeat (STR) polymorphisms have been used as genetic markers in the literature, yet the STR polymorphisms of the DMT1 gene have not been well studied. In this current study, we explored the polymorphisms of the DMT1 gene in a group of elite long-distance runners and controls, by using the PCR-RFLP (Restriction Fragment Length Polymorphism) and Gene scan technology. We found that the genotype frequency of the homozygous 258 bp STR polymorphism of the DMT1 gene (258 bp/258 bp) was significantly higher in the athlete group than in the controls (χ 2 = 14.01, p = 0.006 ) so does the allele frequency of the 258 bp STR polymorphism (χ 2 = 12.867, p = 0.008 ). These data suggested that the STR polymorphism of the DMT1 gene might be correlated with aerobic exercise capacity and the 258 bp homozygous (25 bp/258 bp) could be used as a molecular marker for the talent identification of elite long-distance runners.